bcl-2 protein in non-small-cell lung carcinoma. - Pezzella, F; Turley, H; Kuzu, I; Tungekar, M; Dunnill, MS; Pierce, C; Harris, A; Gatter, K; Mason, D (1993)
BACKGROUND: The proto-oncogene bcl-2 encodes a protein that inhibits programmed cell death (apoptosis). The protein is expressed in basal cells in normal human epithelium, but no data are available on the frequency or clinical importance of its expression in carcinoma. We studied bcl-2 expression in patients with non-small-cell lung carcinoma and correlated this phenomenon with survival. METHODS: Immunochemical analysis with a monoclonal antibody specific for bcl-2 was used to detect the protein in tumor samples from 122 patients undergoing surgery for squamous-cell carcinoma (80 patients) or adenocarcinoma (42 patients). The possibility that bcl-2 expression correlated with survival was investigated with use of the log-rank test, hazard ratios, and their confidence intervals. RESULTS: We detected bcl-2 protein in 25 percent of squamous-cell carcinomas (20 of 80) and 12 percent of adenocarcinomas (5 of 42). In adjacent normal respiratory epithelium, bcl-2 was expressed only in basal cells. Survival at five years was higher among patients with bcl-2-positive tumors, both in the group as a whole (P < 0.1) and in the group with squamous-cell carcinoma (P < 0.02). Patients 60 years of age or older who had bcl-2-positive tumors had the best prognoses, both in the group as a whole (P < 0.02) and in the group with squamous-cell carcinoma (P < 0.01). CONCLUSIONS: The proto-oncogene bcl-2 is abnormally expressed in some lung carcinomas, and its expression may have prognostic importance.